PENINGKATAN PEMAHAMAN LITERASI KEUANGAN PADA SISWA SEKOLAH DASAR - Fathimatus Zahro Fazda Oktavia; Lia Agustina; Anik Kusnawati; Indrayati; Dharmawan Iqbal Akbar; Vuvut Selviana (P3M Politeknik Negeri Malang, 2024)
MI KH Badrussalam is one of the educational institutions at the elementary level located in Malang City. This madrasah has been established since 1926 during the colonial period. In 2022, MI KH Badrussalam has a total of 52 students and 7 teachers. One of the problems of this madrasah related to students is the lack of students' understanding of financial literacy. This is due to the unfavorable economic conditions of the family, so that many financial literacy practices cannot be carried out optimally. However, this does not stop madrasah from continuing to try to grow students' skills in managing finances. Based on the description of the problems above, the PPM team provides training related to financial literacy to increase students' understanding of good financial management. There are three methods that will be used in this activity, namely lecture, discussion and question and answer. The PPM team and partners believe that this training on financial literacy can provide benefits for both parties. The result of this training is that students' knowledge and skills regarding financial literacy increase.